(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
The purpose of this study is to offer insights into Indonesian students’ experiences with using Google Sites-based ePortfolios to learn public speaking, particularly concerning setting objectives, selecting platforms, selecting content, and uploading their ePortfolio. This qualitative research data was gathered from twenty-two students who joined public speaking lesson at an English Language Education Study Program of a university in Yogyakarta, Indonesia, through interviews, observations, and documentation. In-depth interviews were conducted with six selected students of the class and a lecturer who supervised the course. Data analysis is carried out through the process data preparation, reduction and categorization, representation, and conclusion. The study’s findings are as follows: first, while creating an ePortfolio, students desire to have a personal website that serves as a repository for all of their resources, assignments, and completed projects that are structured thoroughly, neatly, and conveniently online. Second, students use Google-Sites, as per the guidelines provided in class, to choose the platform. Students first faced several challenges. Students successfully developed their ePortfolio after learning from friends and instructions from various social media platforms.. Third, students get experience producing and publishing a variety of artifacts, including text, photos, audio, and video, while selecting content.. Four, students gain practice presenting their ePortfolio to instructors and fellow students and engaging in discussion about it when they publish one.